High-efficiency silicon nitride slurry based on photocuring molding and ceramic low-temperature sintering molding method thereof

By using high-refractive index photosensitive resin and oxygen barrier in photocuring molding technology, the curing depth of silicon nitride ceramic slurry is improved, and the bonding performance is improved, which solves the problems of low curing depth and poor mechanical properties of single layers in the prior art, and achieves high-precision, defect-free complex-shaped ceramic printing.

CN119775022AActive Publication Date: 2025-04-08WUHAN UNIV OF TECH

Patent Information

Application Number
CN202411713076.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-27
Publication Date
2025-04-08
Estimated Expiration
2044-11-27

AI Technical Summary

Technical Problem

When the existing photocuring molding technology is used to prepare silicon nitride ceramics, the single layer has a low curing depth and poor mechanical properties after sintering, making it difficult to print out high-precision, defect-free complex-shaped ceramics.

Method used

A photosensitive resin system with high refractive index is adopted to increase the penetration depth of ultraviolet light by reducing the refractive index difference between the resin and the silicon nitride powder, and to increase the curing depth of the silicon nitride slurry with oxygen barriers. At the same time, the high-temperature binder aluminum dihydrogen phosphate is added to improve the bonding performance of the ceramic powder.

Benefits of technology

The silicon nitride ceramic slurry with high solid phase content, low viscosity and excellent curing performance can effectively improve the curing depth of the single layer and the mechanical properties after sintering, and print out high-precision, defect-free silicon nitride blanks.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119775022A_ABST
    Figure CN119775022A_ABST
Patent Text Reader

Abstract

The invention discloses efficient silicon nitride slurry based on photocuring molding and a ceramic low-temperature sintering molding method thereof, and the method comprises the following steps: carrying out ball-milling dispersion on beta-phase silicon nitride powder, a high-temperature binder and a sintering aid in an ethanol solution, and drying and grinding to obtain ceramic mixed powder; the preparation method comprises the following steps: adding a photoinitiator and an oxygen inhibitor into photosensitive resin, and uniformly stirring to obtain a premixed solution; and mixing the ceramic mixed powder with the premixed liquid, adding a dispersing agent and a thixotropic agent, uniformly stirring, and carrying out vacuum defoaming to obtain the silicon nitride ceramic slurry. The technical defect that the single-layer curing thickness of traditional silicon nitride ceramic slurry photocuring forming is low is effectively overcome, high-precision and defect-free samples with the single-layer thickness being 50 micrometers are printed, and the printing efficiency is effectively improved. Meanwhile, a high-temperature binder aluminum dihydrogen phosphate is introduced, and silicon nitride particles are bonded by utilizing metaaluminate generated by decomposition of the aluminum dihydrogen phosphate in the degreasing process, so that the problem of more and larger gaps among the degreased powder is solved, and the preparation of the compact silicon nitride ceramic is realized.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of ceramic additive manufacturing, and in particular relates to a high-efficiency silicon nitride slurry based on photocuring molding and a ceramic low-temperature sintering molding method thereof. Background Art

[0002] As an important structural ceramic, silicon nitride ceramics are widely used in aerospace, military, mechanical engineering, electronics, automobile, chemical and biological fields due to their high temperature resistance, corrosion resistance, wear resistance and unique dielectric properties. They are one of the most promising advanced ceramic materials for extreme environment applications. However, due to their high hardness, excellent strength and brittleness, it is difficult to manufacture porous, special-shaped and other complex Si3N4 parts through traditional molding methods, which limits the application and development of silicon nitride ceramics.

[0003] The development of moldless manufacturing technologies such as photocuring technology has made it possible to prepare ceramics with complex structures. However, the existing photocuring technology has technical defects such as low single-layer curing depth of photocuring and poor mechanical properties after sintering. According to the Beer-Lambert model, the scattering and absorption of powders are the main factors affecting the photocuring characteristics of ceramic slurry. The formula is as follows:

[0004]

[0005] D p -Penetration depth, C d - Curing depth. E0-Exposure energy, formula (2) E c - critical exposure energy, d 50 - average particle size. S- distance between ceramic particles. λ- wavelength. n p -The refractive index (RI) of the ceramic particles, n0-the RI of the resin. Silicon nitride powder has the characteristics of high absorbance and high refractive index (n≈2.1), which is the main reason for the low curing depth of silicon nitride slurry.

[0006] At the same time, due to the layer-by-layer accumulation characteristics of the photocuring forming process, the ceramic powders are basically embedded in the structure of the cross-linked photosensitive resin and the two are closely combined. After degreasing and decarbonization, the macromolecular resin is decomposed, and a large number of gaps appear between the powders. It is difficult to obtain ceramic products with high density after pressureless sintering, making it more difficult to print complex-shaped ceramics with good mechanical properties. Patent CN202210179265 uses a high-refractive-index resin to configure silicon nitride slurry, but it can only slightly increase the curing depth of the slurry and the mechanical properties are relatively weak. Summary of the invention

[0007] The purpose of this section is to summarize some aspects of embodiments of the present invention and briefly introduce some preferred embodiments. Some simplifications or omissions may be made in this section and the specification abstract and the invention title of this application to avoid blurring the purpose of this section, the specification abstract and the invention title, and such simplifications or omissions cannot be used to limit the scope of the present invention.

[0008] In view of the above problems and / or the problems existing in the prior art, the present invention is proposed.

[0009] Therefore, the purpose of the present invention is to overcome the deficiencies in the prior art and provide a high-efficiency silicon nitride slurry based on photocuring.

[0010] In order to solve the above technical problems, the present invention provides the following technical solution: a high-efficiency silicon nitride slurry based on photocuring, characterized in that:

[0011] Including, the high-efficiency silicon nitride slurry based on photocuring is composed of ceramic powder and photosensitive resin, wherein the ceramic powder includes β-phase silicon nitride powder, sintering aid and high-temperature binder, and the photosensitive resin includes resin, photoinitiator, oxygen barrier, dispersant and thixotropic agent;

[0012] In terms of mass fraction, the mass fraction of β-phase silicon nitride powder in the ceramic powder is 86-94%, the mass fraction of sintering aid is 4-8%, and the mass fraction of high-temperature binder is 5-12%;

[0013] The mass fraction of the resin in the photosensitive resin is 90% to 96%, the mass fraction of the photoinitiator is 1 to 3%, the mass fraction of the oxygen inhibitor is 1 to 3%, the mass fraction of the dispersant is 1 to 4%, and the mass fraction of the thixotropic agent is 1 to 5%.

[0014] As a preferred solution of the high-efficiency silicon nitride slurry based on photocuring molding described in the present invention, the mass ratio of the ceramic powder to the photosensitive resin is 1:1.

[0015] As a preferred solution of the high-efficiency silicon nitride slurry based on photocuring molding described in the present invention, the particle size of the β-phase silicon nitride powder is 500nm~5μm; the sintering aid is yttrium oxide powder with a particle size of 0.1~2μm; the high-temperature binder is aluminum dihydrogen phosphate with a particle size of 0.1~2μm.

[0016] As a preferred embodiment of the high-efficiency silicon nitride slurry based on photocuring molding described in the present invention, the resin comprises a mixture of o-phenylphenoxyethyl acrylate and 1,6-hexanediol diacrylate, wherein the content of o-phenylphenoxyethyl acrylate is 60-80wt%, and the content of 1,6-hexanediol diacrylate is 20-40wt%.

[0017] As a preferred embodiment of the high-efficiency silicon nitride slurry based on photocuring molding described in the present invention, the photoinitiator is 2,4,6-trimethylbenzoyl-diphenylphosphine oxide, and the oxygen inhibitor is diisopropylphenyl diphenylamine.

[0018] As a preferred solution of the high-efficiency silicon nitride slurry based on photocuring molding described in the present invention, the dispersant is the wetting dispersant SP710, and the thixotropic agent is octamethylcyclotetrasiloxane.

[0019] The purpose of the present invention is to overcome the deficiencies in the prior art and provide a method for low-temperature sintering of silicon nitride slurry based on photocuring, which is characterized by comprising:

[0020] Silicon nitride powder, sintering aid and aluminum dihydrogen phosphate are mixed and ball-milled to obtain ceramic mixed powder;

[0021] Photosensitive resin monomer, photoinitiator and oxygen inhibitor form a premixed solution;

[0022] The ceramic mixed powder, the premixed liquid, the dispersant and the thixotropic agent are mixed to obtain the silicon nitride ceramic slurry;

[0023] Silicon nitride ceramic slurry is printed by a photocuring printer to form a silicon nitride printed body, which is then cleaned, degreased, decarburized, and sintered.

[0024] As a preferred embodiment of the method of the present invention, the solid content of the silicon nitride ceramic slurry is 40-60 vol%.

[0025] As a preferred embodiment of the method of the present invention, the wavelength of the light source for photocuring is 405 nm, and the light intensity during the curing process is controlled at 6.56-25.36 mw / cm 2 , the curing time is controlled at 4 to 15 seconds; the degreasing-decarburizing process is to heat up to 950 to 1150° C. in a nitrogen atmosphere to remove organic matter and water molecules in aluminum dihydrogen phosphate, and then remove carbon elements in an air atmosphere at 500 to 700° C.

[0026] As a preferred embodiment of the method of the present invention, the sintering is pressureless sintering in a nitrogen atmosphere, the sintering temperature is 1600-1700° C., and the holding time is 2-5 hours.

[0027] Beneficial effects of the present invention:

[0028] The present invention adopts a photosensitive resin system with a high refractive index, and improves the penetration depth of ultraviolet light by reducing the refractive index difference between the resin and the silicon nitride powder. At the same time, an oxygen inhibitor is used to rob oxygen on the surface of the photosensitive resin, reduce the active free radicals combined with oxygen, and improve the curing depth of silicon nitride slurry printing. Silicon nitride ceramic slurry with high solid content, low viscosity and excellent curing performance is configured, which can effectively solve the technical defects of low single-layer curing thickness of traditional silicon nitride ceramic slurry photocuring molding, and is conducive to printing high-precision, defect-free silicon nitride blanks. At the same time, the present invention adds a high-temperature binder (aluminum dihydrogen phosphate) instead of a sintering aid to package and modify the silicon nitride powder. At high temperature, the high-temperature resistant silicon nitride particles are bonded together according to the decomposition of aluminum dihydrogen phosphate to produce type A metaaluminate, so as to achieve the effect of improving the density of the sample. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the following briefly introduces the drawings required for describing the embodiments. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative labor. Among them:

[0030] Figure 1 The present invention is a schematic diagram of the overall process of the photocuring 3D printing of dense silicon nitride ceramic slurry based on a high refractive index resin system and its printing method.

[0031] Figure 2 The effect of the content of the oxygen inhibitor on the curing performance of the silicon nitride slurry. The effect of the content of the oxygen inhibitor KI of 0 to 3 vol% in Example 1-3 and Comparative Example 1-3 on the curing performance of the silicon nitride slurry.

[0032] Figure 3 Interlayer bonding and printing efficiency for different printing layer thicknesses.

[0033] Figure 4 The silicon nitride slurry prepared in Example 1 is used to print a complex model with a single layer thickness of 50 μm, and the model accuracy is tested. Figure 4 (a) is the gyroid printing model. Figure 4 (b) is the BCC printing model. Figure 4 (c) is a test of the model accuracy.

[0034] Figure 5 XRD characterization of silicon nitride ceramics at different temperatures. DETAILED DESCRIPTION

[0035] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, the specific implementation methods of the present invention are described in detail below in conjunction with the embodiments of the specification.

[0036] In the following description, many specific details are set forth to facilitate a full understanding of the present invention, but the present invention may also be implemented in other ways different from those described herein, and those skilled in the art may make similar generalizations without violating the connotation of the present invention. Therefore, the present invention is not limited to the specific embodiments disclosed below.

[0037] Secondly, the term "one embodiment" or "embodiment" as used herein refers to a specific feature, structure, or characteristic that may be included in at least one implementation of the present invention. The term "in one embodiment" that appears in different places in this specification does not necessarily refer to the same embodiment, nor does it refer to a separate or selective embodiment that is mutually exclusive with other embodiments.

[0038] The corresponding relationship between the English abbreviations and full names of the raw materials used in the specific embodiments of the present invention is shown in Table 1.

[0039] Table 1 English abbreviations and full names of raw materials used

[0040]

[0041]

[0042] The raw materials used in the present invention are all commonly available in the market unless otherwise specified.

[0043] Among them, Si3N4 powder was purchased from Shandong Cixing New Materials Co., Ltd., China, photosensitive resin was purchased from Zhongshan Qianyou Chemical Materials Co., Ltd., SP710 dispersant was purchased from Xinbocheng Environmental Protection Materials Co., Ltd., and initiator BAPO was purchased from Fusman Technology (Beijing) Co., Ltd.

[0044] The 3D printer used in the present invention is a CeraStation1.0 ceramic 3D printer developed by QuickDemos Intelligent Manufacturing High-Tech Company to carry out the curing depth test and model printing process.

[0045] The present invention uses a Brookfield-Rheocalc rheometer to test the change in viscosity of the configured ceramic slurry at a shear rate of 0-400 s-1.

[0046] The present invention uses the CeraStation 1.0 ceramic 3D printer developed by QuickDemos Intelligent Manufacturing High-tech Company to print the precision model, and uses a three-dimensional profilometer to observe the minimum side length and the minimum aperture size of the formed blank to judge the forming accuracy of the model.

[0047] Example 1

[0048] This embodiment provides a photocuring 3D printing method and a preparation method of a dense silicon nitride ceramic with excellent curing performance, specifically:

[0049] 1) Weigh the raw materials according to the following formula:

[0050] A total of 300 g of ceramic mixed powder: 270 g of 90% Si3N4 powder (3-5 μm β-Si3N4 powder), 15 g of 5% high-temperature binder aluminum dihydrogen phosphate, and 15 g of 5% sintering aid Y2O3;

[0051] Photosensitive resin premix:

[0052] Mixture: 105.77 g of OPPEOA and HDDA, with volume fractions of 65 vol% and 35 vol%, respectively;

[0053] The mixture contains 2.12g of BAPO, a photoinitiator, which accounts for 2% of the total mass of the photosensitive resin mixture; and 1.59g of KI, an oxygen inhibitor, which accounts for 1.5% of the total mass of the photosensitive resin mixture.

[0054] The volume ratio of the ceramic mixed powder to the photosensitive resin premix is ​​1:1;

[0055] 6 g of dispersant SP710, which is 2% of the mass of the ceramic mixed powder, and 3 g of thixotropic agent D4, which is 1% of the mass of the ceramic mixed powder;

[0056] 2) Preparation of silicon nitride ceramic slurry:

[0057] The ceramic mixed powder raw materials are mixed and placed in a ball mill, anhydrous ethanol and grinding balls are added, and the mixture is ball milled in a planetary ball mill for 4 hours, dried and sieved for later use;

[0058] After mixing the photosensitive resins OPPEOA and HDDA at volume fractions of 65 vol% and 35 vol%, respectively, adding 2 vol% of the photoinitiator BAPO and 1.5 vol% of the oxygen inhibitor KI, the mixture was stirred evenly by a magnetic stirrer to form 109.48 g of a premixed solution;

[0059] After 300 g of the pretreated ceramic mixed powder and 109.58 g of the premixed liquid were mixed, 6 g of a dispersant and 3 g of a thixotropic agent D4 were added in sequence, and the mixture was stirred evenly by a homogenizer and vacuum degassed to obtain a silicon nitride ceramic slurry.

[0060] 3) Characterization of curing performance:

[0061] The CeraStation 1.0 ceramic 3D printer developed by QuickDemos Intelligent Manufacturing High-tech Company was used. The above-mentioned photocurable silicon nitride ceramic slurry was placed in the photocuring molding equipment, and the single-layer curing depth was measured by the photocuring molding method; the wavelength of the light source for photocuring molding was 405nm, and the light intensity during the curing process was adjusted to 6.56-25.63mW / cm 2 , the curing time is 3 to 15 seconds;

[0062] 4) Perform 3D printing:

[0063] Photocuring 3D printing of silicon nitride ceramic slurry uses photocuring 3D printing to obtain silicon nitride printed blanks, and check the interlayer bonding and printing accuracy of the blanks. At the same time, a 3D profiler is used to check the shrinkage and deformation between the blank and the model after printing.

[0064] 5) Degreasing and decarburization:

[0065] After printing, the printed body was ultrasonically cleaned. After cleaning, it was degreased by a two-step degreasing method. First, in a nitrogen atmosphere, the temperature was raised from 5℃ / min to 200℃, then raised to 450℃ at 0.2℃ / min, and kept at this temperature for 2h. Then, the temperature was continued to be raised to 600℃ at 0.5℃ / min, kept at this temperature for 1h, and finally raised to 950℃ at 1℃ / min and kept at this temperature for 2h. After cooling, the temperature was raised to 600℃ at 1℃ / min in an air atmosphere and kept for 2h.

[0066] 6) Silicon nitride ceramic sintering:

[0067] After degreasing, sintering is performed. In a pressureless nitrogen atmosphere, the temperature is raised to 1400°C at 10°C / min, and then to 1650°C at 5°C / min. The temperature is kept for 4 hours to obtain silicon nitride ceramics. The flexural strength and porosity are measured using a mechanical properties tester and the Archimedes drainage method.

[0068] Figure 1 The present invention is an overall flow chart of a high-efficiency silicon nitride slurry based on photocuring molding and a ceramic low-temperature sintering molding method thereof.

[0069] Example 2

[0070] The difference between this embodiment and embodiment 1 is that the content of the oxygen inhibitor is changed to 1 vol% and the mass is 1.06 g. The other process steps and parameters are the same as those in embodiment 1, and different silicon nitride ceramic slurries of this embodiment are obtained. Compared with embodiment 1, under the same light incident intensity, the curing performance of this embodiment is 119.17 μm, which is relatively lower, but the molding surface is flat and no overexposure occurs.

[0071] Example 3

[0072] The difference between this embodiment and embodiment 1 is that the content of the oxygen inhibitor is changed to 2 vol% and the mass is 2.12 g. The other process steps and parameters are the same as those in embodiment 1, and different silicon nitride ceramic slurries of this embodiment are obtained. Compared with embodiment 1, under the same light incident intensity, the curing performance of this embodiment is 136.17 μm, which is relatively lower, but a small amount of whiskers appear on the edge of the molding surface, and there is a small amount of overexposure.

[0073] Comparative Example 1

[0074] The difference between this comparative example and Example 1 is that no oxygen inhibitor is added. Compared with Example 1, under the same light incident intensity, the curing performance of this example is 108.67 μm, which is too low and not conducive to printing.

[0075] Comparative Example 2

[0076] The difference between this comparative example and Example 1 is that the content of the oxygen inhibitor in Example 1 is changed to 2.5%. Compared with Example 1, under the same light incident intensity, the curing performance of this example is 144.33 μm, the curing depth is higher, but a large number of whiskers appear on the edge of the molding surface, there is a serious overexposure phenomenon, and the printed body has obvious warping and deformation.

[0077] Comparative Example 3

[0078] The difference between this comparative example and Example 1 is that the content of the oxygen barrier in Example 1 is changed to 3%. Compared with Example 1, under the same light incident intensity, the curing performance of this example is 148.33 μm, and the curing depth is higher, but excessive whiskers appear on the edge of the molding surface, there is a very serious overexposure phenomenon, the printed body warps and deforms, and it is difficult to mold.

[0079] Figure 2 It is shown that the addition of an oxygen inhibitor can effectively improve the curing performance of silicon nitride slurry, which is conducive to the configuration of a slurry with high curing performance. From Table 1, it can be seen from the data of Example 1 and Comparative Example 1 that as the content of the oxygen inhibitor increases, the curing depth shows an increasing trend. However, when the content of the oxygen inhibitor is too much, a large overexposure will occur in the single-layer curing, resulting in curing at the edge. This will cause edge stress concentration during the printing process and cause the model to warp, which will greatly affect the molding accuracy of the printed model. More preferably, when the content of the oxygen inhibitor is 1vol% to 2vol%, the curing performance of the slurry is better.

[0080] Table 2 Effect of different KI content on the curing performance of ceramic slurry

[0081] Different content of oxygen inhibitor 1% 1.5% 2% 2.5% 3% <![CDATA[Light incident dose (mJ / cm 2 )]]> 256.3 256.3 256.3 256.3 256.3 Curing depth (μm) 119.17 129.67 136.17 144.33 148.33

[0082] Figure 3The interlayer bonding of the model blanks formed by different printing layer thicknesses of the silicon nitride slurry configured for Example 1. It can be clearly seen that after the curing performance is optimized, there are no obvious cracks in the interlayer bonding of the blanks obtained by printing a single layer of 25μm layer thickness and a single layer of 50μm layer thickness, that is, the curing performance we obtained can achieve a sample printed with a single layer of 50μm layer thickness. At the same time, we listed the printing efficiency of different printing layer thicknesses, and it can be found that our silicon nitride slurry system can greatly reduce the printing time and achieve an efficient printing process

[0083] Figure 4 The silicon nitride slurry configured in Example 1 is used to print a complex model with a single layer thickness of 50 μm, and the model accuracy is tested. Figure (a) is a gyroid printing model, (b) is a BCC printing model, and (c) is a test of the model accuracy. It can be found that the silicon nitride slurry configuration method of the present invention can realize the printing process of small pores and complex structure models, and can print a minimum circular aperture radius of 0.3 mm, and an equilateral triangle, square and trapezoid with a minimum side length of 0.5 mm.

[0084] Comparative Example 4

[0085] The difference between this embodiment and embodiment 1 is that aluminum dihydrogen phosphate is replaced by 5 vol% phosphoric acid with a mass of 15 g. The other process steps and parameters are the same as those in embodiment 1, and different silicon nitride ceramic slurries of this embodiment are obtained. Compared with embodiment 1, the curing performance of this embodiment is 127.12 μm under the same light incident intensity. The curing performance does not change much. At 1650°C, the flexural strength after sintering for 4 hours is 165 MPa.

[0086] Comparative Example 5

[0087] The difference between this embodiment and embodiment 1 is that aluminum dihydrogen phosphate is replaced with 5 vol% magnesium hydrogen phosphate with a mass of 15 g. The other process steps and parameters are the same as those in embodiment 1, and different silicon nitride ceramic slurries of this embodiment are obtained. Compared with embodiment 1, the curing performance of this embodiment is 124.52 μm under the same light incident intensity. The curing performance does not change much. At 1650°C, the flexural strength after sintering for 4 hours is 192 Mpa.

[0088] Table 3 Effect of different high temperature binders on mechanical properties

[0089] High temperature adhesive type Phosphoric acid Magnesium hydrogen phosphate Aluminum dihydrogen phosphate Bending strength(Mpa) 165 192 253 Porosity (%) 17.02 12.18 9.31

[0090] It can be seen from Table 3 that at the same temperature and content, the addition of aluminum dihydrogen phosphate in several high-temperature binders is more beneficial to the improvement of the mechanical properties of silicon nitride ceramics after sintering.

[0091] Example 4

[0092] The difference between this embodiment and embodiment 1 is that the content of aluminum dihydrogen phosphate is changed to 8 vol% and the mass is 24 g. The other process steps and parameters are the same as those in embodiment 1, and different silicon nitride ceramic slurries of this embodiment are obtained. Compared with embodiment 1, the curing performance of this embodiment is 126.83 μm under the same light incident intensity. The curing performance does not change much. At 1650°C, the flexural strength after sintering for 4 hours is 272 Mpa.

[0093] Comparative Example 6

[0094] The difference between this embodiment and embodiment 1 is that the content of aluminum dihydrogen phosphate is changed to 10 vol% and the mass is 30 g. The other process steps and parameters are the same as those in embodiment 1, and different silicon nitride ceramic slurries of this embodiment are obtained. Compared with embodiment 1, the curing performance of this embodiment is 123.17 μm under the same light incident intensity. The curing performance does not change much. At 1650°C, the bending strength after sintering for 4 hours is 187Mpa. This is mainly due to the excessive content of aluminum dihydrogen phosphate, which causes decomposition to produce excessive gas, resulting in a decrease in overall density.

[0095] Comparative Example 7

[0096] The difference between this embodiment and embodiment 1 is that the content of aluminum dihydrogen phosphate is changed to 15 vol% and the mass is 36 g. The other process steps and parameters are the same as those in embodiment 1, and different silicon nitride ceramic slurries of this embodiment are obtained. Compared with embodiment 1, the curing performance of this embodiment is 120.67 μm under the same light incident intensity. The curing performance does not change much. At 1650°C, the bending strength is 43Mpa after sintering for 4 hours. This is mainly due to the excessive content of aluminum dihydrogen phosphate, which causes decomposition to produce a large amount of gas, causing the overall density to drop sharply, thereby resulting in an overall decrease in mechanical properties.

[0097] Table 4 Effect of different aluminum dihydrogen phosphate contents on mechanical properties

[0098] Aluminum dihydrogen phosphate content 5% 8% 10% 15% Bending strength(Mpa) 253 272 187 43 Porosity (%) 9.31 8.43 16.56 54.32

[0099] As the content of aluminum dihydrogen phosphate increases, the overall curing properties of the slurry do not change much. At the same time, it can be seen from Table 4 that as the content of aluminum dihydrogen phosphate increases, the mechanical properties show a trend of first increasing and then decreasing. After the degreasing temperature reaches above 950°C, aluminum dihydrogen phosphate reacts to form type A aluminate and forms a strong physical bond with silicon nitride powder to bond silicon nitride powder, shortening the distance between the powders after degreasing. At the same time, when the sintering temperature reaches 1400°C, aluminum dihydrogen phosphate decomposes to form alumina as a sintering aid to further improve the density of the ceramic after sintering, thereby increasing the mechanical properties of silicon nitride ceramics. Therefore, when the content of aluminum dihydrogen phosphate is high, at a higher sintering temperature, excessive aluminum dihydrogen phosphate decomposes and produces gas discharge, which will cause the overall powder to be dispersed, resulting in a decrease in density and reduced mechanical properties.

[0100] Example 6

[0101] The difference between this embodiment and embodiment 1 is that the sintering temperature is changed to 1700°C, and the other process steps and parameters are the same as those in embodiment 1, and different silicon nitride ceramic slurries of this embodiment are obtained. Compared with embodiment 1, the bending strength of this embodiment after sintering for 4 hours is 232Mpa, and there is little difference after sintering.

[0102] Comparative Example 8

[0103] The difference between this comparative example and Example 1 is that the sintering temperature is changed to 1600°C, and the other process steps and parameters are the same as those in Example 1, and different silicon nitride ceramic slurries of this example are obtained. Compared with Example 1, the bending strength of this example after sintering for 4 hours is 170Mpa. This is mainly due to the low sintering temperature, incomplete solid phase reaction of ceramic powder, incomplete grain growth and pore shrinkage, resulting in high porosity and decreased bending strength.

[0104] Comparative Example 9

[0105] The difference between this comparative example and Example 1 is that the sintering temperature is changed to 1750°C, and the other process steps and parameters are the same as those in Example 1, to obtain different silicon nitride ceramic slurries of this example. Compared with Example 1, the bending strength of this example after sintering for 4 hours is 143Mpa, mainly because the sintering temperature is high, and the presence of aluminum dihydrogen phosphate causes the silicon nitride powder to decompose at a lower temperature, resulting in a decrease in overall strength.

[0106] Comparative Example 10

[0107] The difference between this comparative example and Example 1 is that the sintering temperature is changed to 1800°C, and the other process steps and parameters are the same as Example 1 to obtain different silicon nitride ceramic slurries of this example. Compared with Example 1, the bending strength of this example after sintering for 4 hours is 105Mpa, mainly because the sintering temperature is too high, which will aggravate the decomposition of silicon nitride powder, causing the overall strength to drop sharply

[0108] Table 5 Effect of different sintering temperatures on mechanical properties

[0109] Sintering temperature(℃) 1600 1650 1700 1750 1800 Bending strength(Mpa) 170 253 232 143 96 Porosity (%) 13.25 9.31 11.32 18.13 37.53

[0110] Figure 5 XRD characterization of silicon nitride ceramics at different temperatures. Figure 5It can be seen that after degreasing and decarburization, a metaaluminate phase appears, which will combine with the surface of silicon nitride powder to shorten the distance between powders. As the temperature rises, this metaaluminate phase gradually disappears, and the sintered phase Y2SiAlO5N begins to appear. This indicates that after the sintering temperature is further increased, aluminum dihydrogen phosphate decomposes to form alumina as a sintering aid to further improve the density of the ceramic after sintering. At the same time, we can find that when the temperature rises to above 1800℃, an obvious high-temperature decomposition phase of silicon nitride appears.

[0111] It can be seen from Table 5 that at the same amount of aluminum dihydrogen phosphate added, as the temperature increases, the mechanical properties of silicon nitride ceramics show a downward trend. This is mainly because as the temperature increases, the silicon nitride ceramic material will decompose and fail, resulting in a decrease in overall mechanical properties. Too much aluminum dihydrogen phosphate will cause silicon nitride to decompose at a lower temperature, causing the silicon nitride ceramic material to fail as a whole.

[0112] In summary, the present invention adopts high refractive index OPPEOA resin, low viscosity HDDA resin, photoinitiator and oxidation inhibitor to prepare silicon nitride ceramic slurry with high solid content, low viscosity and excellent curing performance. The effect of oxidation inhibitor KI on the curing performance of silicon nitride slurry is utilized to improve the curing performance of silicon nitride slurry, and the curing depth can reach more than 100μm. High-precision, defect-free samples with a single layer thickness of 50μm are achieved, which effectively reduces the printing time and improves the printing efficiency, and is more conducive to the molding process of large-size silicon nitride ceramic samples.

[0113] At the same time, we introduced high-temperature binders and explored the effects of several different high-temperature binders on the sintering process of silicon nitride. We found that aluminum dihydrogen phosphate had a greater improvement on the performance of silicon nitride ceramics after sintering. At the same time, we optimized the sintering temperature and the amount of high-temperature binder added, determined the optimal amount of aluminum dihydrogen phosphate added, and achieved dense sintering of silicon nitride ceramics at a lower temperature, obtaining stronger mechanical properties.

[0114] It should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solutions of the present invention can be modified or replaced by equivalents without departing from the spirit and scope of the technical solutions of the present invention, which should all be included in the scope of the present invention.

Claims

1. A high-efficiency silicon nitride slurry based on photocuring, characterized in that: The high-efficiency silicon nitride slurry based on photocuring is composed of ceramic powder and photosensitive resin, wherein the ceramic powder includes β-phase silicon nitride powder, sintering aid and high-temperature binder, and the photosensitive resin includes resin, photoinitiator, oxygen barrier, dispersant and thixotropic agent; In terms of mass fraction, the mass fraction of β-phase silicon nitride powder in the ceramic powder is 86-94%, the mass fraction of sintering aid is 4-8%, and the mass fraction of high-temperature binder is 5-12%; The mass fraction of the resin in the photosensitive resin is 90% to 96%, the mass fraction of the photoinitiator is 1 to 3%, the mass fraction of the oxygen inhibitor is 1 to 3%, the mass fraction of the dispersant is 1 to 4%, and the mass fraction of the thixotropic agent is 1 to 5%.

2. The high-efficiency silicon nitride slurry based on photocuring as claimed in claim 1, characterized in that: The mass ratio of the ceramic powder to the photosensitive resin is 1:

1.

3. The high-efficiency silicon nitride slurry based on photocuring as claimed in claim 1, characterized in that: The particle size of the β-phase silicon nitride powder is 500nm-5μm; the sintering aid is yttrium oxide powder with a particle size of 0.1-2μm; and the high-temperature binder is aluminum dihydrogen phosphate with a particle size of 0.1-2μm.

4. The high-efficiency silicon nitride slurry based on photocuring as claimed in claim 1, characterized in that: The resin comprises a mixture of o-phenylphenoxyethyl acrylate and 1,6-hexanediol diacrylate, wherein the content of o-phenylphenoxyethyl acrylate is 60-80wt%, and the content of 1,6-hexanediol diacrylate is 20-40wt%.

5. The high-efficiency silicon nitride slurry based on photocuring as claimed in claim 1, characterized in that: The photoinitiator is 2,4,6-trimethylbenzoyl-diphenylphosphine oxide, and the oxygen inhibitor is diisopropylphenyl diphenylamine.

6. The high-efficiency silicon nitride slurry based on photocuring as claimed in claim 1, characterized in that: The dispersant is a wetting dispersant SP710, and the thixotropic agent is octamethylcyclotetrasiloxane.

7. A method for low-temperature sintering of high-efficiency silicon nitride slurry based on photocuring, characterized in that: include, Silicon nitride powder, sintering aid and aluminum dihydrogen phosphate are mixed and ball-milled to obtain ceramic mixed powder; Photosensitive resin monomer, photoinitiator and oxygen inhibitor form a premixed solution; The ceramic mixed powder, the premixed liquid, the dispersant and the thixotropic agent are mixed to obtain the silicon nitride ceramic slurry; Silicon nitride ceramic slurry is printed by a photocuring printer to form a silicon nitride printed body, which is then cleaned, degreased, decarburized, and sintered.

8. The method according to claim 7, characterized in that: The solid content of the silicon nitride ceramic slurry is 40-60 vol%.

9. The method according to claim 7, characterized in that: The wavelength of the light source for photocuring is 405nm, and the light intensity is controlled at 6.56-25.36mw / cm during the curing process. 2 , the curing time is controlled at 4 to 15 seconds; the degreasing-decarburizing process is to heat up to 950 to 1150° C. in a nitrogen atmosphere to remove organic matter and water molecules in aluminum dihydrogen phosphate, and then remove carbon elements in an air atmosphere at 500 to 700° C.

10. The method according to claim 9, characterized in that: The sintering is pressureless sintering in a nitrogen atmosphere, the sintering temperature is 1600-1700° C., and the holding time is 2-5 hours.

Citation Information

Patent Citations

  • Preparation method of light-cured silicon nitride ceramic slurry and silicon nitride ceramic

    CN114524676A

  • Method for preparing low-shrinkage ceramic from photocuring 3D printing hydrogel precursor

    CN116462492A

  • 3DP manufacturing method of aluminum oxide ceramic part

    CN117447190A

  • Preparation method of silicon nitride antenna housing and silicon nitride antenna housing

    CN118495964A

Cited By

  • Photocuring 3D printing-based phosphate enhanced aluminum nitride ceramic and preparation method thereof

    CN121405480A